INSECTICIDAL ACTIVITY OF JATROPHA SEED OIL AGAINST CALLOSOBRUCHUS MACULATUS (FABRICIUS) INFESTING PHASEOLUS ACONITIFOLIUS JACQ - RAVINDRA V; KSHIRSAGAR (The Bioscan, 2010)
The Pulse beetle, Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae) is a cosmopolitan insect pest of Phaseolus aconitifolius Jacq. (Mataki). The insect multiplies very rapidly in storage where it causes very high losses. In the present investigation insecticidal activity of Jatropha seed oil against Callosobruchus maculatus has been carried out. The eggs of C.maculatus were more susceptible to Jatropha oil and shows mortality to all selected dosage. Jatropha seed oil was highly toxic to the eggs of C. maculatus (F = 76.17; p< 0.001) at all dosage levels compared to other pre-adult stages (larvae: F = 65.13; p< 0.001, Pupae: F = 17.43; p< 0.001).